Analisis Strategi Bauran Pemasaran Terhadap Penjualan pada Usaha Dagang RPU Jakarta Timur - Sulaeman, Iman (Jurnal Indonesia Sosial Sains, 2021)
Informants in this study were business owners and employees of RPU's Trading Business (UD). RPU is an abbreviation of the name UD which cannot be mentioned because the privacy of the business owner does not allow it. This study aims to analyze the marketing mix strategy on sales at the East Jakarta RPU trading business. This type of research used a qualitative approach, with data collection techniques using interviews and observations. Data analysis technique in this research is using spiral data analysis technique. The results showed that UD RPU sells products made from beef, chicken and goat. UD RPU creates new innovations by producing new products with high quality and with more attractive product variations. The price of the product on the UD RPU is still not fixed, because the owner does not provide a definite price for each product sold, the price can change according to the condition of the goods offered and the fluctuating purchase price. The location of UD RPU is indeed strategic because it is in the meat warehouse area and next to the market, but the business location needs to expand both online and open other selling points. So far, promotions have been carried out by UD RPU directly and also through online media such as the Tokopedia marketplace. Thus, it can be concluded that UD RPU sells processed beef, chicken and goat products in a quite strategic area, with innovative products of high quality but unstable prices because the owner adapts to the existing conditions.